Utilization of nanomaterials and ceramic waste for sustainable environmental protection - Jegatheeswaran D.; Sridhar J.; Saranya S.; Gokulan R.; Gasim H. (Global NEST, 2024)
The amount and type of waste are increasing due to population growth. Many harmful materials have been in the atmosphere for a very long times. This causes a crisis in the waste disposal and thereby contributes to environmental issues. Recycling concrete manufacturing waste materials not only offers a resource for producing concrete of top standard but also aids in correctly addressing the issue of waste disposal. Due to the leftover ceramic powder's high resistance and inability to be processed by any recycling process, using it in concrete is a good use for it. Using powdered ceramic waste in concrete as a pozzolana, their strength and water absorption were explored. The samples were made with 15% and 20% porcelain dust waste substitutes. Simultaneous effects were determined by using 0.5% and 1% nano-alumina and 15% and 20% waste ceramic powder. compression power, tests for water absorption, and weight and strength loss tests were accomplished. After 7 and 28 days of curing for nano-alumina at 0.5%, the increases in compressive strength are 11.46% and 10.22%, respectively. After 7 and 28 days of curing for 1% of the nano-alumina, the increases in compressive strength are 16.25% and 14.73%, respectively. The findings indicate that the compressive strength of the concrete is not significantly harmed by the inclusion of ceramic waste up to 20%. Additionally, the use of pozzolana, ceramic waste powder, and nano-alumina increases compressive strength while lowering the ability to absorb water. Consequently, nano-alumina can enhance the impacts of ceramic waste powder on concrete's characteristics. 2023 Global NEST.